Water erosion on soil slopes and a suggested method for assessing susceptibility of mine tailings to water erosion - Muasi, Vhonani Shadrack (My University, 2006)
Environmental impacts from tailings impoundments differ according to their mineral constituents. Erosion is one of the processes that aggravate the environmental impacts from tailings due to the transportation of particles, and knowing the susceptibility mechanisms of those tailings particles for erosion will provide understanding of how to prevent impacts arising from erosion. Laboratory pinhole erosion tests were used to determine the susceptibility of tailings particles to erosion. Compacted tailings samples were used, as compaction is an important parameter of erosion susceptibility. The study entails investigation of factors that affect erosion from the slopes of tailings deposits in order to evaluate mitigation measures. The results could help to provide more effective methods to reduce gully formation and enhance environmental protection. It is advisable to prevent environmental impacts at the source, before they become detrimental and costly to mitigate.
Student Number : 0418755N - MSc (Eng) dissertation - School of Civil and Environmental Engineering - Faculty of Engineering and the Built Environment
Keywords: water erosion; soil slopes; pinhole erosion; test and mine tailings